Acute Macular Neuroretinopathy following Coronavirus Disease 2019 Vaccination - Mambretti, Manuela; Huemer, Josef; Torregrossa, Giulia; Ullrich, Marlies; Findl, Oliver; Casalino, Giuseppe (Ocular immunology and inflammation, 2021)
Purpose: To report acute macular neuroretinopathy (AMN) in two young women two days after receiving Vaxzevria Coronavirus disease (COVID-19) vaccination. Methods: Observational case reports. Observation: The first patient was an Italian 22-year-old female with acute onset of paracentral scotoma two days post vaccination. The second patient was an Austrian 28-year-old female who presented with sudden onset paracentral scotoma two days after vaccination. Multimodal retinal imaging was consistent with AMN in both cases. Both patients were on long-term oral contraceptives, had no history of COVID-19 and experienced one-day duration fever the day after the vaccination. Conclusions: Vaccination may represent a possible risk factor for AMN onset in women on oral contraceptives. We encourage ophthalmologists to investigate recent vaccination status when dealing with new onset AMN. Further studies are needed to assess the link between vaccinations and AMN.